Predictors Of Postoperative Surgical Site Infection Following Abdominal Surgeries In Hospitals: A Prospective Cohort Study (The Review of Diabetic Studies, 2025)
Background: Surgical site infection (SSI) following abdominal surgery remains a significant cause of patient morbidity, prolonged hospitalization, and increased healthcare costs. Identifying key predictors is essential for developing targeted prevention strategies.Methods: A prospective cohort study was conducted among 320 adult patients undergoing abdominal surgeries in a hospital setting. Data on patient demographics, clinical characteristics, surgical factors, and perioperative practices were collected. Patients were followed for 30 days postoperatively to assess for SSI, defined based on standard clinical criteria. Bivariate and multivariate logistic regression analyses were used to identify factors associated with SSI.Results: The overall incidence of postoperative SSI was 16.3% (n=52). Superficial incisional infections were most common (53.8%). Significant predictors of SSI identified included diabetes mellitus, obesity, emergency surgery, surgical duration >2 hours, contaminated/dirty wound classification, and inappropriate timing of prophylactic antibiotics.Conclusion: Postoperative SSI is a frequent complication of abdominal surgery. The findings highlight the multifactorial nature of SSI risk, emphasizing the need for comprehensive preoperative risk assessment, strict adherence to infection prevention protocols—particularly regarding antibiotic timing and wound management—and tailored interventions for high-risk patients to improve surgical outcomes.